2018
DOI: 10.4066/biomedicalresearch.29-18-410
|View full text |Cite
|
Sign up to set email alerts
|

A reliable and accurate system of joint position sense measurement

Abstract: Objective: Measurement of range of motion is used to measure the joint Position Sense (JPS). The objective of this study was to give an easy and less costly method of measuring JPS. Methods: The study conducted at Tehran University of Medical Sciences, in Iran in May 2017. In this study researcher used the system of digital photographs, non-reflective markers and software for measuring the accuracy and reliability. The fixed arm of the goniometer was horizontal. The moveable arm was positioned at the 15° initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Olyayi, in a similar study, used the image capture technique by digital camera for the shoulder joint at angles of 30, 45, 65, and 70 degrees while the goniometer was attached to the joint. The obtained results of absolute and relative error of each angle (0.97) showed excellent inter-day reliability of the technique [23]. One of the limitations of their study was its small sample size, which limits the possibility of generalizing the results.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Olyayi, in a similar study, used the image capture technique by digital camera for the shoulder joint at angles of 30, 45, 65, and 70 degrees while the goniometer was attached to the joint. The obtained results of absolute and relative error of each angle (0.97) showed excellent inter-day reliability of the technique [23]. One of the limitations of their study was its small sample size, which limits the possibility of generalizing the results.…”
Section: Discussionmentioning
confidence: 91%
“…This technique has been proposed as an acceptable method for measuring the joint position sense of lower limbs [21,22]. However, few studies have mea-sured the joint position sense of upper limbs by this technique [23,24]. Olyayi used the image capture technique in a case study and reported its good reliability [23], but for better knowledge, we need a study with a larger sample size.…”
Section: Proprioception Joint Position Sense Upper Limb Image Capture Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, simultaneous alignment of the goniometer's two arms with the bones forming the joint may hinder free joint movement, thus affecting measurement accuracy [39]. Some researchers combine a goniometer examination with photography, which certainly increases the measurement accuracy, but is very time-consuming [15]. Other types of research have evaluated JPS using camera-based motion capture systems.…”
Section: Discussionmentioning
confidence: 99%
“…The JPS test involves a position matching procedure in which a target joint position is presented, and the test subject must actively recreate that position (so-called end angle) [14]. JPS is usually measured by goniometers, digital photography, or a camera-based system [15][16][17][18]. We found only one study that used inertial sensors to test JPS [13].…”
Section: Introductionmentioning
confidence: 99%